MAKNA ENTERPRENEUR BAGI WIRAUSAHA MUDA BERSTATUS MAHASISWA DI AREA CAR FREE DAY KOTA PEKANBARU - Rezi Ryantino; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The more advanced a country, the more educated people are, and the more unemployed people the more the world of entrepreneurship is felt. The success of development is supported by an entrepreneurial spirit that can be launched by employment. Economic progress will improve welfare. Students as young pulse entrepreneurs are new. The profession of being an entrepreneur is no longer something else and is not only done by students who are weak in the economy, because many are found as part-time workers as young entrepreneurs. From this phenomenon, there are entrepreneurial entrepreneurs who are next to each other and discriminated against in friends. The purpose of this study was to find out the meaning of entrepreneurs for young student entrepreneurs in the area of Pekanbaru's car free day, to find out the motives of young entrepreneurial students in the car free day area of Pekanbaru City, and to find out communication for young students in the car free day area. Pekanbaru City. This research uses qualitative research methods using phenomenological and informant retrieval using purposive of 5 people. With the technique of collecting data with interviews, and documentation. As for the technique of checking the validity of the data, researchers used the extension technique. The data obtained is then processed for reduction, so as to produce general conclusions. The results of this study indicate that the motives of entrepreneurs for young entrepreneurial students in the Car Free Day area of Pekanbaru City are divided into two motives because (Because of Motives) there is a sense of need and interest, while the motives for (Agar Motif) seek the identity they want. the meaning of entrepreneurs for young entrepreneurs in the area of Pekanbaru's Car Free Day is independent or not dependent on others, always working in work, having responsibility, and responsibility, a fighter, not easily discouraged, and brave enough to face risks. The experience of communicating young entrepreneurs with the status of students in the car free day area of Pekanbaru City is divided into two positive communication experiences which can make parents happy, have a good relationship with the social environment (residence) and have good relationships with campus friends, and negative communication experiences namely people people who are poor because they are looking for money to study, are shunned by school friends because they realize that friends who like people who are not able to be friends. And negative thinking from the social environment of our house that people think is only a self-sufficient person, he still has parents who support his life even though he doesn't try on his ow  Keywords: Mean, Enterpreneur, Student